Diffusion coefficients in multiphase Ni80Cr20-Ti system - Wierzba, Bartek; Serafin, Daria; Nowak, Wojciech J.; Wierzba, Patrycja; Ciećko, Andrzej; Mazurkow, Aleksander (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
In this paper, the reactive diffusion in Ni80C20r–Ti ternary system is discussed at 1173 K. The diffusion couple was prepared and annealed for 100 h. The two intermetallic phases and two two-phase zones occur, namely,Ti2Ni, TiNi, TiNi+Cr and TiNi3+Cr. Using the experimental results, the molar fractions and thicknesses of the intermetallic phases, the intrinsic diffusion coefficients in each phase were approximated. The Wagner method was used in the pure intermetallic phases. In the two phase zone the approximation was based on the generalized Darken method. The presented methods allowed for determination of the diffusion coefficients in each presented phase.
Keywords: reaction diffusion; equilibrium; Ni80Cr20–Ti system